Improving the Performance of Photovoltaic Cells Using Pure and Combined Phase Change Materials: Numerical Study Using ANSYS Fluent - ALIAT SOUFIANE; BOUREZMA SADDAM (University of Shahid Hama Lakhdar - El Oued, 2025)
Photovoltaic (PV) systems suffer from performance losses in hot climates due to excessive heat. This study investigates the use of phase change material (PCM) for passive thermal regulation of PV panels. A 2D transient numerical model was developed in ANSYS Fluent to simulate heat transfer and phase change under desert-like conditions. Results show that integrating RT28HC paraffin PCM reduced surface temperature by up to 6.1 °C and improved electrical efficiency by 2.75%. These findings confirm the effectiveness of PCM as a passive cooling solution to enhance PV performance in high-temperature environments تعاني الأنظمة الكهروضوئية من انخفاض في الأداء في المناطق الحارة بسبب تراكم الحرارة. تهدف هذه الدراسة إلى تحليل تأثير استخدام مادة متغيرة الطور (PCM) كحل تبريد سلبي للألواح الشمسية. تم تطوير نموذج عددي ثنائي الأبعاد غير مستقر باستخدام برنامج ANSYS Fluent لمحاكاة انتقال الحرارة وتغير الطور في ظروف مناخية صحراوية. أظهرت النتائج أن دمج مادة البارافين RT28HC أدى إلى خفض درجة حرارة السطح بما يصل إلى 1.6 °C وتحسين 5%. تؤكد هذه النتائج فعالية المواد متغيرة الطور كحل .. الكفاءة الكهربائية بنسبة 5 تبريد سلبي لتحسين أداء الألواح الشمسية في المناطق الحارة
Master's thesis specializing in energy.2025
Keywords: Photovoltaic panels; Passive cooling; Phase change material; ANSYS Fluent; Thermal performance; Efficiency enhancement: ا لألواح الكهروضوئية، التبريد السلبي، المواد متغيرة الطور، ANSYS Fluent ، الأداء الحراري، تحسين الكفاءة